Cloud-assisted gamification for education and learning – Recent advances and challenges - Hakak, Saqib Iqbal; Noor, Nurul Fazmidar Mohd; Ayub, Mohamad Nizam; Pal, Hannyzurra; Hussin, Nornazlita; Ahmed, Ejaz; Imran, Muhammad (Elsevier, 2019)
Gamification has gained considerable interest in education circles due to its capability of enhancing the learning process among students. In the future, it is expected that gamification will overtake the traditional way of learning resulting in issues such as scalability, upgradation of learning modules. To address these issues, merging gamification with cloud computing seems a viable solution. However, the employability of gamification through cloud computing is still in its infant stage. Hence, this article investigates the applicability of gamification through cloud computing and presents a comprehensive survey of state-of-the-art gamification in education and learning. We also identify the subject areas that can be gamified and taught using the cloud service. The critical elements and minimum requirements necessary to gamify education are also identified. Moreover, a specific cloud-assisted gamification architecture is proposed and discussed together with its possible applications. The article is concluded with the research challenges and suggestions for future work.